Sonographic Prediction of Pediatric Renal Scarring With Full Parameter Normalization. (14th June 2016) - Stember, Joseph N.; Lynch, Dustin; Behr, Gerald; Alam, Shumyle
Abstract : Objectives: To predict the chronic kidney disease (CKD) state for pediatric patients based on scaled renal cortical echogenicity. Methods: Sonograms from a cohort of 26 patients, half of whom had stage 4 or 5 CKD, whereas the other half had normal renal function, were analyzed. For each patient image, a region of interest (ROI) was drawn around the renal cortex for comparison with an ROI drawn around the hepatic parenchyma. The latter ROI was shifted spatially to normalize the signal attenuations and time‐gain compensations of the two organs' ROIs. Then the average pixel intensity of the renal ROI was divided by the corresponding hepatic value, resulting in scaled renal cortical echogenicity. Results: The average scaled renal cortical echogenicity was higher for diseased than healthy kidneys by roughly a factor of 2 (2.01 [95% confidence interval, 1.62–2.40] versus 1.05 [95% confidence interval, 0.88–1.23] for normal kidneys). This difference was statistically significant ( P < .001). Conclusions: Our results show that the pediatric CKD state correlates with rigorously calculated scaled renal cortical echogenicity.